Design and simulation of high-swing fully differential telescopic Op-Amp - Zahra Pezeshki (Computer Science and Information Technologies, 2021)
This article describes the process of design and simulation of a high-swing fully differential telescopic operational amplifier (Op-Amp). Due to the common gate-common Source (CG and CS) cascode structure, the gain is very high. To maximize this gain, the load must also be selected such as two current sources. This circuit has the higher voltage in output than current Op-Amps in accordance with desirable characteristics. The loss of power of this operating amplifier are very low and in milliwatts. With use of a power supply of 1.8 V, it achieves a high-swing 1.2 V, a differential gain of 76.333 dB, and 50 dB CMRR. This new design through the simulations and analytically shows that the high-swing fully differential telescopic Op-Amp retains its high CMRR even at high frequencies.